The impact of the use of certain motor exercises in the development of diverse physical abilities and motor skills and some of the basic volleyball - Abdullah , Jian (Journal of Physical Education, 2011)
Aim of the research: Detection of an exercise in the development of various motor and the development of physical abilities and mobility of some basic skills and ball flight. The research Sample: Students in the third academic year in the Department of Physical Education / College of Basic Education Mustansiriya University. Research Methodology: Experimental method has been used for relevance to the nature and purpose of the research. Conclusions: • the various motor exercises used in the current study had a positive impact on the development and effective and some basic skills and physical abilities and motor skills for volleyball in the experimental group. • more than the experimental group members who used an exercise program on the various kinetic control group in the development of some basic skills and physical abilities and mobility of the ball flight.